Statistical Characterization of the Chunk Size Distribution in DASH - Vaca-Rubio, Cristian J.; Gómez-Paredes, Gerardo; Aguayo-Torres, María del Carmen; López-Martínez, Francisco Javier (My University, 2019)
We present a statistical characterization of the segment size distribution of video streaming services based on dynamic adaptive streaming over HTTP (DASH). We ﬁrst obtain the empirical distributions from trafﬁc captures of available data sets encoded with different quality and segment size duration. Then, we determine the distributions that provide a better ﬁt to the empirical data. We show that Weibull and truncated logistic distributions are adequate to modeling the chunk size distributions for a wide range of video qualities and segment size duration. Results are used to develop a source model for DASH trafﬁc, implementing a synthetic generator of DASH-like video traces.
Keywords: Transmisión digital; DASH; Traffic model; Streaming